Gibberellic acid and abscisic acid coordinately regulate cytoplasmic calcium and secretory activity in barley aleurone protoplasts. - Gilroy, S (1992)
The effects of gibberellic acid (GA3) and abscisic acid (ABA) on the temporal and spatial dynamics of cytosolic calcium concentration ([Ca2+]i) in aleurone protoplasts of barley (Hordeum vulgare L. cv. Himalaya) were measured by using fluorescence ratio analysis and confocal microscopy. After 4-6 h of treatment, GA3 induced a sustained increase in [Ca2+]i from 50 to 150 nM in aleurone protoplasts. The increase in [Ca2+]i preceded the GA3-induced increase in alpha-amylase synthesis and secretion by 4 h. The elevation of [Ca2+]i was highest in the peripheral cytoplasm and may play a role in coordinating the secretory events there. Reducing Ca2+ levels in the incubation medium to below 500 microM inhibited the increase in [Ca2+]i and the GA3-induced stimulation of alpha-amylase synthesis and secretion. These data suggest that GA3 may increase [Ca2+]i by increasing the influx of Ca2+ at the plasma membrane. ABA reversed the effect of GA3 on [Ca2+]i within 3 h, 2 h before its effect on alpha-amylase production could be detected. Thus changes in [Ca2+]i may play a role in mediating the effects of GA3 and ABA on the synthesis and secretion of alpha-amylase in the aleurone cell.